Rethinking the paradigm: How comparative studies on fatty acid oxidation inform our understanding of T cell metabolism. Issue 2 (December 2015) - Chiaranunt, Pailin; Ferrara, James L.M.; Byersdorfer, Craig A.
Highlights: Alloreactive T cells during graft- versus -host disease increase their reliance on fatty acid oxidation. Key pathways of FAO regulation are conserved across tissue types and yield insight into similar potential mechanisms in alloreactive T cells. T cell metabolic reprogramming is dynamic and context-dependent. Abstract: The classic paradigm of T cell metabolism posits that activated Teff cells utilize glycolysis to keep pace with increased energetic demands, while resting and Tmem cells rely on the oxidation of fat. In contrast, Teff cells during graft- versus -host disease (GVHD) increase their reliance on oxidative metabolism and, in particular, on fatty acid oxidation (FAO). To explore the potential mechanisms driving adoption of this alternative metabolism, we first review key pathways regulating FAO across a variety of disparate tissue types, including liver, heart, and skeletal muscle. Based upon these comparative studies, we then outline a consensus network of transcriptional and signaling pathways that predict a model for regulating FAO in Teff cells during GVHD. This model raises important implications about the dynamic nature of metabolic reprogramming in T cells and suggests exciting future directions for further study of in vivo T cell metabolism.